Sentencing criminals / Maznah Kamaruddin - Kamaruddin, Maznah (Faculty of Law, 1987)
"Sentence" as defines in The Concise Oxford Dictionary means punishment alloted to persons condemned in a Criminal trial. Justice Abd Hamid assumed that "sentencing" means the act of imposing punishment in such criminal trial. Sentencing, broadly defined, includes all those decisions the courts make with regard to the official handling of a person who pleads guilty or is convicted of a crime. This may include probation, without or with specified restrictions on the behaviour of the defendant, imposition of a fine, capital punishment, commitment under a special statue such as as sexual psychopath law, work assignments restitution to the victim, corporal punishment, incarceration or a combination of forms of punishments